Essentials of medical biochemistry : with clinical cases - Bhagavan, N. V. (Elsevier/Academic Press, 2011)
Expert biochemist N.V. Bhagavan's new work condenses his successful Medical Biochemistry texts along with numerous case studies, to act as an extensive review and reference guide for both students and experts alike. The research-driven content includes four-color illustrations throughout to develop an understanding of the events and processes that are occurring at both the molecular and macrolecular levels of physiologic regulation, clinical effects, and interactions. Using thorough introductions, end of chapter reviews, fact-filled tables, and related multiple-choice questions, Bhagavan provides the reader with the most condensed yet detailed biochemistry overview available. More than a quick survey, this comprehensive text includes USMLE sample exams from Bhagavan himself, a previous coauthor. * Clinical focus emphasizing relevant physiologic and pathophysiologic biochemical concepts * Interactive multiple-choice questions to prep for USMLE exams * Clinical case studies for understanding basic science, diagnosis, and treatment of human diseases * Instructional overview figures, flowcharts, and tables to enhance understanding.